2013
DOI: 10.31729/jnma.2193
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Bacteriuria in Pregnant Women

Abstract: Introduction: Asymptomatic bacteriuria is the significant presence of bacteria in urine of an individual without symptoms. The aim of the study is to determine the prevalence of asymptomaticbacteriuria in pregnant women. Methods: This study was a prospective study conducted in the department of Obstetrics and Gynaecology at B. P. Koirala Institute of Health Sciences. The duration of the study was six monthsfrom January to June 2012. A total of 600 pregnant women were enrolled. All women were clinically i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
2
7
0
1
Order By: Relevance
“…Our results are consistent with most previous studies, in which Escherichia coli was the most commonly identified etiological factor of asymptomatic bacteriuria during gestation [8,13,19,29,32] . However, some studies found that is the commonest causative pathogen of asymptomatic bacteriuria in pregnant women is Klebsiella [12,24,37,38] .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are consistent with most previous studies, in which Escherichia coli was the most commonly identified etiological factor of asymptomatic bacteriuria during gestation [8,13,19,29,32] . However, some studies found that is the commonest causative pathogen of asymptomatic bacteriuria in pregnant women is Klebsiella [12,24,37,38] .…”
Section: Discussionsupporting
confidence: 93%
“…These results are in accordance with some studies, which showed no significant difference in the incidence of asymptomatic bacteriuria with parity [13-15, 20, 30, 32, 33, 35, 40, 41] . However, other studies reported a significant association between the incidence of asymptomatic bacteriuria and increasing parity [12,21,26,29,42] .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Respecto al tipo de infección urinaria más frecuente en los resultados del presente estudio, la prevalencia de bacteriuria asintomática es del 7,69%, resultado cercano al 8,7% encontrado en Dharan (Nepal) por Thakur y col., 31 ; aunque levemente mayor al 6,1% descrito por Ahmad y col., 32 en un grupo de 392 embarazadas en Srinagar, Kashmir (India); no obstante, en un reciente estudio publicado por Sandhya y col. 33 en el mismo país, se encontró una prevalencia ligeramente mayor (9,2%) en 250 gestantes. Con relación a la cistitis aguda, los hallazgos de este estudio, difieren del 1,3% reportado por Harris y col., 7 en el Centro médico Wilford Hall, San Antonio, Texas (EEUU), en una muestra de 9734 mujeres; así como al 54% descrito por Sanín-Ramírez y col., 34 en Medellín (Colombia), diferencia explicable porque las pacientes tenían síntomas de infección del tracto urinario.…”
Section: Discussionunclassified